Fashion Business Performance In Surabaya - Agustina, Tri Siwi; Dewi, Alvita Komala (Universitas Muhammadiyah Sidoarjo, 2021)
The COVID-19 pandemic, which resulted in social and physical restrictions, has consequences for the sustainability of the fashion business. This industry is included in the top 5 priority scales for MSME development in Surabaya. Therefore, the existence of the fashion industry is very important for the economy of Surabaya. Related to this, fashion business owners in Surabaya are required to be able to maintain their business through work innovation. This study aims to analyze the direct or indirect influences of competence, the use of information technology, and self-efficacy on business performance through work innovation as a mediating variable for fashion entrepreneurs in Surabaya. This research is a quantitative involving 69 fashion entrepreneurs who are supported by the Surabaya Trade Office. Data distribution was carried out using online questionnaires from November to December 2020. Hypothesis testing was carried out by the path analysis. The results of this study include: competence and self-efficacy are proven to have a positive influence on business performance; the use of information technology is proven to not influence business performance; work innovation cannot mediate the influence of competence on business performance; work innovation is proven to fully mediate the influence of the information technology usage on business performance; work innovation is proven to mediate some of the self-efficacy influence on business performance.